Vaginal birth vs caesarean delivery: impact on gastroschisis anatomy in newborns (a 33-year experience) - O.K. Sliepov; N.Y. Zhylka; V.L. Veselskyi; N.Y. Skrypchenko; T.V. Avramenko; M.Y. Myhur; O.P. Ponomarenko (Publishing House TRILIST, 2021)
Background. Despite the existence of numerous studies on the optimal delivery mode in gastroschisis (GS), their results remain controversial. Therefore, the presented study is focused on establishing the delivery mode impact on GS anatomy in newborns. Research objective. The study was conducted to determine the impact of the delivery mode on the features of GS anatomy in newborns. Materials and methods. A retrospective analysis of medical records of 135 pregnant women and 135 their newborns with GS born between 1987 and 2020 was conducted. All newborns are divided into 3 groups. Newborns delivered by caesarean section are included in group I (n = 80); children born exclusively naturally are included in groups II (n = 25) and III (n = 30). The following anatomical features of GS in newborns were studied: localization and size of the anterior abdominal wall defect, confluence with the abdominal cavity, the nature and frequency of the eventrated organs. Results. The size of the anterior abdominal wall defect was significantly smaller in children with GS delivered by caesarean section (3.02 ± 0.58 cm; p < 0.01) than in children born naturally (4.17 ± 0.3 cm in group II, 4.7 ± 0.29 cm in group III). The frequency of retroperitoneal organs eventration was significantly less (20.0%; p < 0.01) in caesarean delivery grope than in II and III groups (52% and 63.3%, respectively). There was no significant difference in frequency of other abdominal organs eventration, localization of the anterior abdominal wall defect and confluence with the abdominal cavity. Level of evidence - III. Conclusions. The mode of delivery affects the size of abdominal wall defect and frequency of the abdominal organs eventration in newborns with GS.